Enzyme-linked immunosorbent assay typing of California serogroup viruses isolated in Canada. - Artsob, H (1984)
A procedure was developed to type California serogroup viruses by an antibody-capture, enzyme-linked immunosorbent assay. Seven California serogroup members from North America were distinguished, including snowshoe hare, La Crosse, California encephalitis, San Angelo, Jamestown Canyon, Keystone, and trivittatus. Extensive cross-reactions were observed between Jamestown Canyon and the closely related South River strain. The enzyme-linked immunosorbent assay method was successfully applied to the typing of 77 California serogroup viruses isolated in Canada, including 61 snowshoe hare, 13 Jamestown Canyon, and 3 trivittatus topotypes.